Strategic interactions between fiscal and monetary authorities in a multi-country new-Keynesian model of a monetary union - Tomasz Michalak; Jacob Engwerda; Joseph Plasmans (Center for Economic Studies and ifo Institute (CESifo), 2009)
In this paper we consider a number of key issues related to the policy coordination in a monetary union that has been recently discussed in the literature. To this end we propose a multi-country New-Keynesian model of a monetary union cast in the framework of linear quadratic differential games. Our framework can be used to simulate strategic interactions between an arbitrary number of fiscal authorities interacting in coalitions with or against the common central bank. For many parameter combinations our results confirm the findings of Beetsma et al. (2001) that for symmetric inflation and output gap shocks, fiscal coordination between all the countries is counter-productive within a monetary union. The clash between the central bank and the coalition of national governments is most intense under a symmetric inflation shocks when there is strong conflict concerning the orientation of stabilisation policies. This conflict is less pronounced under an asymmetric inflation and output gap shocks, however, still makes fiscal cooperation unattractive. We extend the existing New-Keynesian literature on policy coordination by considering not only cases of non-coordination, fiscal cooperation and the grand coalition, but also the partial cooperation arrangements between fiscal players. We show that, in many cases, partial fiscal coordination of a subgroup of fiscal players is more efficient, from the social point of view, than non-coordination. However, this regime still delivers poor results from the perspective of individual players. This occurs especially in the case of asymmetric shocks, as the countries directly affected by the shocks tend to export losses to the countries with whom they form a coalition. Furthermore, we show that the common objective of the grand coalition is of the upmost importance for the outcome of the stabilisation process.
Keywords: C70; E17; E58; E61; E63; 330; Macroeconomic stabilisation; EMU; policy coordination; linear quadratic differential games; Finanzpolitik; Geldpolitik; Internationale wirtschaftspolitische Koordination; Konjunkturpolitik; Währungsunion; Spieltheorie; Ungleichgewichtstheorie; Mehr-Länder-Modell; Theorie